2021
DOI: 10.3389/fmicb.2021.678406
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Growth Inhibition of Bread Spoilage Fungi by Different Preservative Concentrations Using a Rapid Turbidimetric Assay System

Abstract: Bread and intermediate moisture bakery products are mainly spoiled by yeasts and filamentous fungi. The inoculum load and preservation system used determines their shelf life. To extend the shelf life of such commodities, the use of chemical preservatives is the most common way to try and control the initiation of mold spoilage of bread. This study has utilized a rapid turbidimetric assay system (Bioscreen C) to examine the temporal efficacy of calcium propionate (CP) and potassium sorbate (PS) for controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…For every P. variotii strain used in this study, a higher MIC for sorbic acid was found than previously reported for a P. variotii strain isolated from a South American soft drink production facility (Stratford et al, 2009). In another study, a P. variotii strain isolated from bakery products was able to grow at extremely high concentrations of potassium sorbate up until 128 mM in Yeast Extract Sucrose broth at pH 5.0 (Garcia et al, 2021). This concentration corresponds to 45 mM undissociated sorbic acid, which is more than 4 times higher than the highest MIC found in this study.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…For every P. variotii strain used in this study, a higher MIC for sorbic acid was found than previously reported for a P. variotii strain isolated from a South American soft drink production facility (Stratford et al, 2009). In another study, a P. variotii strain isolated from bakery products was able to grow at extremely high concentrations of potassium sorbate up until 128 mM in Yeast Extract Sucrose broth at pH 5.0 (Garcia et al, 2021). This concentration corresponds to 45 mM undissociated sorbic acid, which is more than 4 times higher than the highest MIC found in this study.…”
Section: Discussionsupporting
confidence: 39%
“…Minimum inhibitory concentrations (MICs) for sorbic acid were 1.4 -4.4-fold higher when compared to that of a P. variotii strain isolated from a South American soft drink facility (Stratford et al, 2009). On the other hand, up to four time higher MIC values were found for a P. variotii strain isolated from bakery products, albeit in a different experimental setup (Garcia et al, 2021). Although heat resistance was not significantly correlated with sorbic or benzoic acid resistance, the two most sorbic acid resistant strains, DTO 195-F2 and DTO 282-E5, were also heat resistant.…”
Section: Most Problematic Paecilomyces Variotii Strains For Food Indu...mentioning
confidence: 87%
See 1 more Smart Citation
“…About 1% acetic acid prevents the proliferation of Clostridium botulinum and the consequent production of toxin in cucumber fermentations brined with 6% NaCl (Ito et al., 1976; Koukou et al., 2021). Potassium sorbate was incorporated into the fermentation cover brines anticipating that the activity of the indigenous yeasts and molds could induce undesirable chemical and physical changes in the vegetables (Etchells et al., 1961; Garcia et al., 2021; Guillou et al., 1992; Mehyar et al., 2011; Pérez‐Díaz et al., 2015; Stratford et al., 2020). Yeast growth is sporadically observed in vegetable fermentations particularly under aerobic conditions and with shredded substrates (Etchells et al., 1947).…”
Section: Resultsmentioning
confidence: 99%
“…Commonly found food-spoiling Ascomycetes include, for example, A. niger, Paecilomyces variotii and Penicillium roqueforti [2]. Therefore, preservative resistances of Ascomycetes have been investigated before, especially in relation to specific food products such as bread [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%